2015
DOI: 10.1039/c5cc04186d
|View full text |Cite
|
Sign up to set email alerts
|

Programmed assembly of 4,2′:6′,4′′-terpyridine derivatives into porous, on-surface networks

Abstract: The use of divergent, V-shaped, 4,2':6',4''-terpyridine building blocks that self-assemble into hydrogen-bonded domains and upon addition of copper atoms undergo metallation with concomitant transformation into a coordination network is described; multiple energetically similar structural motifs are observed in both hydrogen-bonded and adatom-coordinated networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Solution-based coordination assemblies using 4′-(1H-imidazol-4-yl)-4,2′:6′,4′′tpy (Chart 2) as the organic linker involve only the outer Ndonors of the 4,2′:6′,4′′-tpy unit 26 but in contrast, the Ndonors of the 4,2′:6′,4′′-tpy and imidazolyl units are involved in binding copper adatoms when the latter are added to an assembly of the ligand on an Au(111) surface. 25 We now demonstrate that this switch in coordination behavior is also observed for ligands 1−3. Compounds 1−3, differing only by the presence of an H, Me, or Et 2-substituent on the pyrimidin-5-yl functionality (Chart 3 and Figure 3) were deposited under UHV conditions by thermal sublimation.…”
Section: ■ On-surface Assembliessupporting
confidence: 61%
See 1 more Smart Citation
“…Solution-based coordination assemblies using 4′-(1H-imidazol-4-yl)-4,2′:6′,4′′tpy (Chart 2) as the organic linker involve only the outer Ndonors of the 4,2′:6′,4′′-tpy unit 26 but in contrast, the Ndonors of the 4,2′:6′,4′′-tpy and imidazolyl units are involved in binding copper adatoms when the latter are added to an assembly of the ligand on an Au(111) surface. 25 We now demonstrate that this switch in coordination behavior is also observed for ligands 1−3. Compounds 1−3, differing only by the presence of an H, Me, or Et 2-substituent on the pyrimidin-5-yl functionality (Chart 3 and Figure 3) were deposited under UHV conditions by thermal sublimation.…”
Section: ■ On-surface Assembliessupporting
confidence: 61%
“…4′-(1H-Imidazol-4-yl)-4,2′:6′,4′′-tpy forms hydrogen-bonded domains on an Au(111) surface, and the addition of copper adatoms results in reorganization into a 2D coordination network; the N-donors of both the 4,2′:6′,4′′-tpy and imidazolyl units are bonded to copper. 25 In the only example of a coordination assembly involving 4′-(1H-imidazol-4-yl)-4,2′:6′,4′′-tpy under solution conditions, the imidazolyl unit is uncoordinated. 26 We have also shown that 1 and its 2-methyl-substituted derivative 2 bind zinc(II) selectively through the 4,2′:6′,4′′-tpy domain.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The two type terpyridine ligands can coordinate with metal ions in the outer pyridine rings, while the central pyridine rings are usually not involved in coordination [ 2 , 11 ]. The inter-ring C–C bond rotations have no effect on the ligand conformer ( Figure 1 c), and therefore 4,2′:6′,4′′-terpyridine, which acts as an excellent V-shaped building block, has received increasing attention [ 2 , 4 , 5 , 12 ]. There are over 200 types of complexes, which have been reported with this type of terpyridine in coordination polymers and networks etc.…”
Section: Introductionmentioning
confidence: 99%
“…There are over 200 types of complexes, which have been reported with this type of terpyridine in coordination polymers and networks etc. [ 2 , 4 , 5 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33] Pyridine units are a specially interesting substituent to drive molecular selfassembly. 34,35 This group allows the formation of double hydrogen-bonds (C-H/N) between neighboring molecules. Numerous pyridine-based molecular building blocks have been synthesized 36,37 and various nanoarchitectures have been engineered using these compounds.…”
Section: Introductionmentioning
confidence: 99%